Linking the water-energy-food nexus and sustainable development indicators for the Mediterranean region. (August 2018) - Saladini, F.; Betti, G.; Ferragina, E.; Bouraoui, F.; Cupertino, S.; Canitano, G.; Gigliotti, M.; Autino, A.; Pulselli, F.M.; Riccaboni, A.; Bidoglio, G.; Bastianoni, S.
Highlights: PRIMA promotes sustainable food production and water provision in the Med area. PRIMA can foster the achievement of SDGs in Mediterranean countries. A monitoring tool made of 12 indicators (+ 4 at low scale) will track PRIMA progress. Abstract: Water use and agricultural practices in the Mediterranean area are unsustainable. The situation is worsened by the increased frequency of droughts and floods, as well as desertification and soil depletion, associated with climate change. The aim of Partnership for Research and Innovation in the Mediterranean Area (PRIMA) is to foster an integrated programme of sustainable food production and water provision in the framework of the water-energy-food nexus. A monitoring tool developed under PRIMA is based on the Sustainable Development Goals, two of which are specifically dedicated to food security (SDG 2) and sustainable management of water (SDG 6). The 12 indicators that have been chosen to be monitored in the Mediterranean area are: Multidimensional Poverty Index (MPI); population overweight (%); land use (%); GHG emissions (total and AFOLU)(tCO2e ); cereal yield (kg/ha); agriculture value added (US$/worker); fertilizer consumption (kg/haarable land ); crop water productivity (kg/m 3 ); annual freshwater withdrawal for agriculture (%); population served using with safely managed water service (rural, %); population served using with safely managed sanitation (rural, %); amount of agricultural residues used for energy purposes (t). Datasets for these indicators are collected by international bodies such as the World Bank, WHO, FAO and UNFCCC; recent series are available for almost all Mediterranean countries and are constantly updated. The aim of the proposed monitoring tool is to keep track of the impact generated in by PRIMA research and innovation projects Mediterranean countries.